Exercise Interventions for Cancer Survivors: A Meta-Analysis of Quality of Life Outcomes - Rebecca A. Ferrer; Tania B. Huedo‐Medina; Blair T. Johnson; Stacey M. Ryan; Linda S. Pescatello (2010)
Exercise improves quality of life (QOL) in cancer survivors, although characteristics of efficacious exercise interventions for this population have not been identified.